Combined NK1 antagonism and serotonin reuptake inhibition: effects on emotional processing in humans. (May 2013) - Harmer, Catherine J; Dawson, Gerry R; Dourish, Colin T; Favaron, Elisa; Parsons, Elizabeth; Fiore, Monica; Zucchetto, Mauro; Bifone, Angelo; Poggesi, Italo; Fernandes, Sofia; Alexander, Robert C; Goodwin, Guy M
Background: Synergistic effects of NK1 receptor antagonism combined with serotonin reuptake inhibition have been reported in preclinical models. GSK424887 is a selective competitive antagonist of the human NK1 receptor and inhibitor of the serotonin transporter. However, its actions in human models of depression have not been assessed. Methods: This study explored the effects of acute administration of GSK424887 compared to placebo in healthy male volunteers. The selective serotonin reuptake inhibitor (SSRI) citalopram was used as a positive control. A battery of emotional processing tasks was given at the peak time of drug effect. Results: GSK424887 enhanced attentional vigilance in the dot-probe task to both positive and negative stimuli. By contrast, citalopram enhanced perception of angry, sad and happy facial expressions and increased positive bias in the facial expression recognition task. Neither drug significantly affected emotion potentiated startle responses or emotional memory. Conclusions: These results suggest that acute administration of GSK424887 modulated some aspects of emotional processing but these effects were not similar to those seen previously with antidepressant agents. This was the first use of the battery of emotional processing tasks in a Phase 1 study. Repeated administration of the test and active control drugs may be needed to reliably characterise their effects.